NO, ROS, RAS, and PVAT: More Than a Soup of Letters - Barp, Clarissa Germano; Bonaventura, Daniella; Assreuy, Jamil (Frontiers in Physiology, 2021)
Perivascular adipose tissue (PVAT) has recently entered in the realm of cardiovascular diseases as a putative target for intervention. Notwithstanding its relevance, there is still a long way before the role of PVAT in physiology and pathology is fully understood. The general idea that PVAT anti-contractile effect is beneficial and its pro-contractile effect is harmful is being questioned by several reports. The role of some of PVAT important products or systems such as NO, ROS and RAS may vary depending on the context, disease, place of production, etc what adds more doubts on how mediators of PVAT anti- and pro-contractile effects are called to action and their final result. This short review will address some points regarding NO, ROS and RAS in the beneficial and harmful roles of PVAT.